Realised Selection Response Under Four Methods Of Selection In Third And Fourth Cycles In A Set Of Brinjal Lines - Jessy Kutty PC (Department Of Olericulture, College Of Horticulture, 1985)
Selection methods like mass, single plant, pure line and single seed descent were efficiently used to exploit the genetic variability present in the transgressive segregants of the brinjal line SM 6, keeping the bacterial wilt resistance of the population intact. The present study conducted at the College of Horticulture, Vellanikkara, extended the comparison of the selection methods for further improvement of the eleven genetic groups within the line SM 6 for earliness and productive characters in the third and fourth cycles of selection. The criteria for selecting the elite plant types were fruits/plant and yield/plant. Observations were recorded on earliness, vegetative characters and productive characters. The eleven genetic groups were evaluated under each selection method for the characters under study. The genetic groups SM 6 – 2, SM 6 – 4, SM 6 – 7 and SM 6 - 1 were promising for fruits/plant and total yield/plant. Only promising lines were carried forward in the fourth cycle of selection. The relative efficiency of the four methods of selection to improve economic characters was critically examined. Being a cross pollinated crop mass selection and single plant selection were superior to pure line selection and single seed descent selection to improve economic characters. Genetic information like genotypic coefficient of variation, phenotypic coefficient of variation, heritability in the broad sense, genetic advance and genetic advance as percentage of mean were higher for progenies developed through single plant selection. Realised genetic gain for economic characters as compared to the overall mean was positive for progenies developed through mass and single plant selection methods. The level of resistance of SM 6 to bacterial wilt, under four methods of selection, was assessed. Single seed descent and single plant selection methods were found effective in the fourth cycle of selection to improve level of resistance of SM 6 to bacterial wilt. When screened under field condition the line SM 6 – 7 was found immune to bacterial wilt, while the lines SM 6 – 2 and SM 6 – 4 were found highly resistant. Four resistant lines SM 45, SM 56, SM 71 and SM 74 were grown for comparison with SM 6. These lines were found moderately resistant and were late and low yielders.